Diagnosis and Therapy of Bronchopulmonary Carcinoid Tumors - Sen WEI (Chinese Journal of Lung Cancer, 2011)
Bronchopulmonary carcinoid tumors are relatively uncommon neoplasms and typically benign and slow growing. However, more aggressive subtypes may develop early nodal and distant metastases. The clinical presentation allows prediction of the diagnosis and cell type and directs evaluation and treatment. Young age, central tumor, and no nodal enlargement are highly suggestive of typical carcinoid. These patients require no further diagnostic or staging tests beyond chest computed tomography and bronchoscopy before resection. For a high suspicion of atypical carcinoid (central cN2, peripheral cN1,2), imaging for distant, metastases and mediastinoscopy is suggested, with multimodality treatment for an atypical carcinoid with N2 involvement. Because these tumors are generally resistant to chemotherapy, complete surgical resection is the primary form of therapy. Long-term survival for patients with typical carcinoid is excellent but is decreased in those with the atypical subtype. Complete tumor resection with preservation of uninvolved pulmonary parenchyma remains the fundamental goal in the surgical treatment of this unusual clinical entity.